2011
DOI: 10.1098/rsbl.2011.0103
|View full text |Cite
|
Sign up to set email alerts
|

Dome-shaped functional response induced by nutrient imbalance of the prey

Abstract: Nutritional ecological theory predicts that predators should adjust prey capture and consumption rates depending on the prey's nutritional composition. This would affect the predator's functional response, at least at high prey densities, i.e. near predator satiation. Using a simple fruitfly-wolf spider laboratory system in Petri dishes, we found that functional responses changed from day to day over a 7 day period. After 1 to 2 days of feeding, dome-shaped functional responses (i.e. reduced predation at highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 21 publications
(25 reference statements)
1
25
1
Order By: Relevance
“…Conversely, if some prey species contain a higher concentration of lipid than is optimal, then predators should switch their focus towards more protein-rich prey species. A functional response matching this scenario was recently documented in wolf spiders (Pardosa amentata), which increased capture rate at increasing prey density when prey was protein-rich but reduced capture rate above a certain prey density when the prey was lipid-rich [51].…”
Section: Results (A) Effects Of Lipid and Protein Intake On Egg Produmentioning
confidence: 99%
“…Conversely, if some prey species contain a higher concentration of lipid than is optimal, then predators should switch their focus towards more protein-rich prey species. A functional response matching this scenario was recently documented in wolf spiders (Pardosa amentata), which increased capture rate at increasing prey density when prey was protein-rich but reduced capture rate above a certain prey density when the prey was lipid-rich [51].…”
Section: Results (A) Effects Of Lipid and Protein Intake On Egg Produmentioning
confidence: 99%
“…When hunting individually, male weasels Mustela nivalis nivalis had higher predation rates than females (Sundell, 2003), while female wolf spiders Pardosa vancouveri had higher rates than males (Hardman and Turnbull, 1974). Both age and hunger level can then impact predation rates: starved damselflies Ischnura elegans had higher predation rates than satiated conspecifics (Akre and Johnson, 1979; see also Bressenford and Toft, 2011); sub-adult pumas have lower kill rates than adults, possibly because experience makes pumas more effective predators (Knopff et al, 2010). As with predation risk and prey selection, predation rate thus seems to vary between individuals and such variability can be structured according to phenotypic attributes.…”
Section: Impact On the Strength Of The Responsementioning
confidence: 96%
“…variability may not be uncommon, especially among species that exhibit prey switching with size or age. For example, owing to changing nutritional needs during different life stages, adult wolf spiders Pardosa amentata have a Type II functional response for protein-rich fruit flies Drosophila melanogaster and a dome-shaped response for lipid-rich fruit flies, while sub-adult spiders display the opposite pattern (Bressenford and Toft, 2011). Putra and Yasuda (2006) examined larval hoverflies Eupeodes corolla preying on aphids Acyrthosiphon pisum and found that first instars had a unimodal response to prey density, second instars had a Type II curve, and third instars had a Type I (linear) response.…”
Section: Impact On the Type Of Responsementioning
confidence: 99%
“…According to nutritional ecology theory, the type of a predator's functional response may vary because predators must adjust their prey capture and consumption rates to the nutritional composition of the prey and other factors (Bressendorff and Toff 2011).…”
Section: Discussionmentioning
confidence: 99%